The wrestler - Mortensen, John Kenn, 1978- (2025)
"Freestyle wrestler The Sledgehammer has never met defeat, not at the hands of Painkiller, Handsome Jens, or the Angel of Death. Despite this, twenty-five years past his glory days, he's a washed-up, guilt-ridden alcoholic with no friends or family. While he's brawling in a back alley, an expensive car rolls up. The man inside will take him on a surreal journey, where heavy metal mixes with Greek myth by way of Faust. But Sledgehammer's greatest victory lies outside the ring..."--